IMPLEMENTASI MANAJEMEN PANGKAT DAN JABATAN PEGAWAI NEGERI SIPIL SEBAGAI UPAYA MEWUJUDKAN GOOD GOVERNANCE DI LINGKUNGAN PEMERINTAH KABUPATEN DEMAK - Andrianto, Okky; Suparnyo, Suparnyo; SULISTYOWATI, SULISTYOWATI (Jurnal Suara Keadilan, 2020)
Abstract The study entitled Management Implementation Rank and Position Civil Servants as Effort to Realize Good Governance in Environmental District Government Demak is motivated bureaucratic reforms in the system of governance (good governance), especially the arrangement of human resources personnel with management ranks and positions of civil servants to realize the civil service state apparatus in order to perform their duties professionally and responsibility in carrying out the tasks of the government.This research was conducted in order to determine implementation management ranks and positions of civil servants to achieve good governance in Demak regency government environment and to determine government policy Demak to optimize the management ranks and positions of civil servants in order to realize good governance.The method used by the author is juridical empirical data collection was done using interview guide with research sites in the Civil Service Agency, Education and Training Demak and processing of data with descriptive analysis.The results of this study indicate that the implementation of management ranks and positions of civil servants Governments Demak district in accordance with Law No. 5 of 2014 on State Civil Reform and Government Regulation No. 11 of 2017 concerning civil service management, but some longer guided by the provisions considering there are no technical regulations that govern. PolicyDemak regency government to optimize the management ranks and positions of civil servants in order to realize good governance based on the principles or the basic principles of good governance (good governance) which is in line with the Grand Design State Civil Administrative Development 2020-2024. Use of information systems in the civil service merit-based civil service agency, Education and Training Demak is used for the management ranks and positions of civil servants in local government environment in order to simplify, speed up the process flow of personnel services. Keywords : management, rank, position, civil servants, good governance  Abstrak Penelitian dengan judul Implementasi Manajemen Pangkat dan Jabatan Pegawai Negeri Sipil sebagai Upaya Mewujudkan Good Governance di Lingkungan Pemerintah Kabupaten Demak ini dilatarbelakangi  reformasi birokrasi dalam sistem tata kelola pemerintahan yang baik (good governance) terutama penataan sumber daya manusia aparatur dengan manajemen pangkat dan jabatan PNS untuk mewujudkan PNS sebagai aparatur negara agar dapat melaksanakan tugas secara profesional dan tanggungjawab dalam melaksanakan tugas pemerintahan.Penelitian ini dilakukan dengan tujuan untuk mengetahui implementasi manajemen kepangkatan dan jabatan PNS untuk mewujudkan Good Governance di lingkungan Pemerintah Kabupaten Demak dan untuk mengetahui kebijakan Pemerintah Kabupaten Demak untuk mengoptimalkan manajemen pangkat dan jabatan PNS dalam rangka mewujudkan Good Governance.Metode pendekatan yang digunakan penulis adalah yuridis empiris dengan pengambilan data dilakukan dengan menggunakan pedoman wawancara dengan lokasi penelitian di Badan Kepegawaian, Pendidikan dan Pelatihan Kabupaten Demak dan pengolahan data dengan deskriptif analisis.Hasil penelitian ini menunjukkan bahwa implementasi manajemen pangkat dan jabatan PNS di Lingkungan Pemerintah Kabupaten Demak sesuai dengan Undang-Undang Nomor 5 Tahun 2014 tentang Aparatur Sipil Negara dan Peraturan Pemerintah Nomor 11 Tahun 2017 tentang Manajemen PNS, tetapi beberapa berpedoman pada ketentuan lama mengingat belum ada regulasi teknis yang mengatur. Kebijakan Pemerintah Kabupaten Demak untuk mengoptimalkan manajemen pangkat dan jabatan PNS dalam rangka mewujudkan Good Governance berdasarkan asas-asas atau prinsip-prinsip  dasar good governance (tata kelola pemerintahan yang baik) yang sejalan dengan Grand Design Pembangunan Aparatur Sipil Negara 2020-2024. Pemanfaatan sistem informasi berbasis sistem merit PNS pada Badan Kepegawaian, Pendidikan dan Pelatihan Kabupaten Demak digunakan untuk manajemen pangkat dan jabatan PNS di Lingkungan Pemerintah Kabupaten dalam rangka mempermudah, mempercepat alur proses pelayanan kepegawaian.Kata kunci : manajemen, pangkat, jabatan, PNS, good governance